2011
DOI: 10.1021/je200819r
|View full text |Cite
|
Sign up to set email alerts
|

Complex Stability and Molecular Structure Studies of Divalent Metal Ion with l-Norleucine and Vitamin B3

Abstract: The stability constants of L-norleucine (Nle) and nicotinic acid (NA) with divalent metal ion (Cu 2+ , Ni 2+ , and Co 2+ ) binary and mixed ligand systems at 298 K and ionic strength 0.15 mol 3 dm À3 NaNO 3 water solutions were determined using pHpotentiometry. The stability constants data were estimated using the HYPERQUAD 2008 program, and each complex species was shown graphically using the HySS program. UVÀvisible spectrophotometric measurements were performed to prove the complex species formation. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Overall formation constants of ferulic acid and gallic acid in the absence and presence of the metal ions were acquired from the previous research. , These values together with the overall formation constants of metal ions with G, GG, and GGG were introduced to the HYPERQUAD 2008 program as constants and used for determination of mixed-ligand complex stability involving metal ions, phenolic acids (A), and glycine peptides (P), as reported in Tables and . With regard to the metal ions, an identical trend as the Irving–William series was observed in all systems (GA-G, GA-GG, GA-GGG, FA-G, FA-GG, and FA-GGG) in which these ligands bound to the metal ions and formed the most and the least stable complex with copper and cobalt, respectively.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Overall formation constants of ferulic acid and gallic acid in the absence and presence of the metal ions were acquired from the previous research. , These values together with the overall formation constants of metal ions with G, GG, and GGG were introduced to the HYPERQUAD 2008 program as constants and used for determination of mixed-ligand complex stability involving metal ions, phenolic acids (A), and glycine peptides (P), as reported in Tables and . With regard to the metal ions, an identical trend as the Irving–William series was observed in all systems (GA-G, GA-GG, GA-GGG, FA-G, FA-GG, and FA-GGG) in which these ligands bound to the metal ions and formed the most and the least stable complex with copper and cobalt, respectively.…”
Section: Resultssupporting
confidence: 61%
“…The study of complex formation between metal ions and antioxidant ferulic acid (FA) or gallic acid (GA) in water in the presence of some nonproteinogenic amino acids or soluble vitamins has been gained much attention from our research group in the last three years. A thorough literature review showed that no work seems to have been done on the study of complexation between metal ions, phenolic acids, and glycine peptides in aqueous solutions. In the present work, the previously studied ligands were used to mimic a biological system in which phenolic acid acts as an antioxidant, while glycine (G) and its small peptides act as building blocks of enzymes or protein that show their importance in biological reactions. The amide nitrogen in the peptide backbone is known to be a potential binding site for metal ions; these metal ions will induce the deprotonation of the amide nitrogen in peptide bonds, thus forming a stable chelate ring with the metal ion. So, in addition to determining the complex stability constant, it is necessary to study the influence of amide nitrogen deprotonation in glycylglycine (GG) and glycylglycylglycine (GGG) peptide bonds on the complex stability.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the protonation and stability constants of SHAM, PHEN and their metal complexes, Hyperquad2008 was used to make nonlinear least square curve fitting based on experimental pH-potentiometric titration data as described in our previous work [17,[7][8][9][10][11][12][13][14]. Various models with possible compositions of complex species and estimation of its stability constants were proposed to the program.…”
Section: Equilibrium Data Analysismentioning
confidence: 99%
“…These materials have been used as drugs and they are reported to possess a wide range of biological activities against bacteria, fungi and certain types of tumors. In a continuation of our research work oriented towards studying the acid-base and complexation equilibria of many biological oxygen and nitrogen donor drugs with different chelating property [7][8][9][10][11][12][13][14], the present work concerns the equilibrium studies and synthesis of some binary and mixed ligand complexes involving salicylhydroxamic acid, 1,10-phenanthroline.Most interest in the design of binary and ternary complexes as drugs has been centered on the area of antimicrobial and anticancer agents. Hereby, in this paper, we report the results of the equilibrium studies and synthesis of binary and ternary complexes of salicylhydroxamic acid (SHAM) and 1,10-phenanthroline (PHEN) (Scheme 1) as well as investigated their antibacterial and antifungal activities in order to orient future investigations towards the finding of new potent and safe antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Experts have embattled numerous traditional or common drugs in similar of contemporary medicine to recognize and extract vigorous ingredients for the medication development. Research interest on the interactions of bioactive ligands with different metal ions have been increased during the last decade in my laboratory [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Recently, the experimental protonation and complex formation equilibrium constants of nicotine (NIC) with trivalent (iron(III), and chromium(III)) and divalent (copper(II), and nickel(II)) metal ions have been investigated in aqueous solutions using pH-potentiometric, and cyclic voltammetry techniques [42].…”
Section: Introductionmentioning
confidence: 99%